Knockdown of DNMT1 and DNMT3a Promotes the Angiogenesis of Human Mesenchymal Stem Cells Leading to Arterial Specific Differentiation. (13th February 2016) - Zhang, Rui; Wang, Nan; Zhang, Li‐Nan; Huang, Na; Song, Tie‐Feng; Li, Zheng‐Zheng; Li, Man; Luo, Xue‐Gang; Zhou, Hao; He, Hong‐Peng; Zhang, Xiao‐Yu; Ma, Wenjian; et al.
Abstract: Human mesenchymal stem cells (hMSCs) possess the potential to differentiate into endothelial cells (EC). DNA methylation plays an important role in cell differentiation during development. However, the role of the DNA methyltransferases Dnmt1 and Dnmt3a in specific arterial differentiation of hMSCs is not clear. Here, we show that the CpG islands in the promoter regions of the EC specification and arterial marker genes were highly methylated in hMSCs based on bisulfite genomic sequencing. Treatment with the DNMT inhibitor 5‐aza‐dc induced the reactivation of EC specification and arterial marker genes by promoting demethylation of these genes as well as stimulating tube‐like structure formation. The hMSCs with stable knockdown of Dnmt1/Dnmt3a were highly angiogenic and expressed several arterial specific transcription factors and marker genes. A Matrigel plug assay confirmed that Dnmt1/Dnmt3a stable knockdown hMSCs enhanced blood vessel formation compared with WT MSCs. We also identified that the transcription factor E2F1 could upregulate the transcription of arterial marker genes by binding to the promoters of arterial genes, suggesting its critical role for arterial specification. Moreover, miRNA gain/loss‐of‐function analyses revealed that miR152 and miR30a were involved in endothelial differentiation of hMSCs by targeting Dnmt1 and Dnmt3a, respectively. Taken together, these data suggest that Dnmt1 and Dnmt3a are critical regulators for epigenetic silencing of EC marker genes and that E2F1 plays an important role in promoting arterial cell determination. Stem Cells 2016;34:1273–1283